Optimization of design for floors, roofs and vaults - Branco, Jorge M. (2012)
Typical horizontal elements in historic buildings are represented by timber floors and roofs and masonry vaults. All these components have a crucial role in seismic area, as they are required to resist under lateral loads, to improve the global behaviour through effective connections and to distribute forces, with proper in-plane stiffness, to the shear Walls. Niker project, by the Work Package 5 (WP5) “Optimization of design for ﬂoors, roofs and vaults”, gave the opportunity to compare various strengthening solutions applied to representative components present in existing buildings, taking into account the variety of types on a regional scale, and considering as priority the selection and use of compatible techniques and materials and/or minimum interventions. These solutions are intended to preserve the existing horizontal elements by improving their mechanical performance, as needed to keep their structural contribution on the overall behaviour, thus avoiding generalized substitutions. The validation of strengthening techniques applicable to existing buildings was carried out by means of comprehensive laboratory experimental campaigns, the results of which were used to calibrate numerical models. Materials characterization and on-site investigations provided additional data to increase knowledge and calibrate models. On the basis of these results, parametric studies were performed, to support the design and assessment components. In the paper, the main results obtained on the horizontal components are described.